Method for preparing flaky aluminum oxide by using electrolyte waste liquid and flaky aluminum oxide
By using electrolyte waste liquid and a composite molten salt system to prepare sheet-like alumina, the problems of equipment corrosion and environmental pressure caused by the use of fluorides and strong acids in the existing technology have been solved, and low-cost green production of sheet-like alumina with high aspect ratio has been achieved.
Patent Information
- Application Number
- CN202511535717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-27
- Publication Date
- 2026-01-09
AI Technical Summary
The existing molten salt method for preparing sheet alumina requires the use of fluorides and strong acids, which leads to high equipment corrosion risk, significant environmental impact, and high production costs.
Using waste electrolyte as the aluminum source, aluminum hydroxide precipitate is formed through carbon dioxide carbonation reaction. It is then combined with a composite molten salt system of soluble sodium chloride, potassium chloride and sodium sulfate to carry out molten salt reaction. The sodium content is controlled and flake alumina is prepared by washing with hot water, avoiding the use of fluorides and strong acids.
High aspect ratio sheet-like alumina can be produced without the use of fluorides and strong acids, reducing production costs, equipment corrosion and environmental pressure, and achieving green and environmentally friendly production.
Smart Images

Figure CN121292490A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of alumina preparation, and particularly relates to a method for preparing flaky alumina using electrolyte waste liquid and flaky alumina. BACKGROUND
[0002] Flaky alumina is a functional alumina material with special crystal morphology. The crystal grows along the {0001} basal plane and presents a hexagonal flaky or lamellar structure. Flaky alumina has a large diameter-thickness ratio and obvious anisotropic thermal conductivity, and also has excellent electrical insulation and mechanical reinforcement, and is widely used in high-end technical fields such as thermal interface materials, electronic packaging, structural ceramic composites and pearl pigments. At present, the preparation methods of flaky alumina mainly include hydrothermal method, sol-gel method, solid phase sintering method and molten salt method. Among them, the molten salt method can promote the formation of α-Al2O3 at a lower temperature and realize the basal plane directional growth, and is the most promising technical route at present.
[0003] The existing molten salt method includes: (1) taking industrial-grade sodium aluminate solution as raw material, precipitating the industrial-grade sodium aluminate solution to obtain a precipitate, calcining the precipitate to obtain a precursor, and finally synthesizing flaky alumina products with a particle size of 2-18 μm in a molten salt system. (2) Introducing a shaping agent in the molten salt system, forming alumina crude products in the molten salt system, and then using hydrofluoric acid to acidify the alumina crude products to obtain flaky alumina products with a high diameter-thickness ratio. (3) Adding aluminum fluoride as a mineralizer in the NaCl-KCl composite molten salt system. This kind of mineralizer can reduce the reaction temperature of the aluminum source into alumina and accelerate the growth of alumina crystals to form flaky alumina products. (4) Adding α-Al2O3 seeds in the Na2SO4 / K2SO4 and halide composite molten salt system to induce the transformation of aluminum source into flaky alumina products. This reaction system can obtain flaky alumina products with controllable size. (5) Using calcined Al(OH)3 powder or amorphous alumina powder generated by γ-Al2O3 powder to replace the traditional aluminum source. By adding α-Al2O3 seed powder in the amorphous alumina powder, flaky alumina products can be formed at a lower reaction temperature (660-1300 °C).
[0004] Although the existing molten salt method has made great progress in reducing the synthesis temperature of flaky alumina and modifying the parameters of flaky alumina, a large amount of molten salt system is generally needed, and most of them need to add fluorides to improve the morphology of alumina, or use strong acid to modify after forming flaky alumina crude products, in order to obtain flaky alumina products with a high diameter-thickness ratio. The use of fluorides or strong acids will increase the corrosion resistance of the equipment and the environmental pressure, making the cost of the current molten salt system for producing flaky alumina products relatively high. SUMMARY
[0005] The application provides a method for preparing flaky alumina using electrolyte waste liquid and flaky alumina, to solve the technical problem of how to prepare flaky alumina with high aspect ratio without using fluoride and strong acid.
[0006] In a first aspect, the embodiments of the application provide a method for preparing flaky alumina using electrolyte waste liquid, the electrolyte waste liquid containing sodium ions and aluminum ions, the molar concentration of the aluminum ions being greater than or equal to 0.5 mol / L, the method comprising: carbonating the electrolyte waste liquid using carbon dioxide, so that the aluminum ions form aluminum hydroxide, to obtain aluminum hydroxide precipitate; first washing the aluminum hydroxide precipitate using a detergent, to obtain washed aluminum hydroxide solid phase with a preset sodium content; calcining the washed aluminum hydroxide solid phase with a preset sodium content, to obtain gamma-type alumina precursor; carrying out molten salt reaction on the gamma-type alumina precursor and a composite molten salt system, so that the gamma-type alumina precursor grows along the crystal basal plane, to obtain flaky alumina crude product; wherein the composite molten salt system is a mixture of sodium chloride, potassium chloride and sodium sulfate; second washing the flaky alumina crude product, to obtain flaky alumina product.
[0007] Optionally, the mass m1 of the composite molten salt system and the mass m2 of the gamma-type alumina precursor satisfy: m1:m2=(2 to 6):1.
[0008] Optionally, the amount of substance n1 of the sodium chloride, the amount of substance n2 of the potassium chloride and the amount of substance n3 of the sodium sulfate satisfy: n1:n2:n3=(0.8 to 2):(0.5 to 1.5):(0.8 to 1.5).
[0009] Optionally, the temperature of the molten salt reaction is 950°C to 1200°C, and the time of the molten salt reaction is 1h to 24h.
[0010] Optionally, the temperature of the calcination is 450°C to 850°C, and the time of the calcination is 0.5h to 10.0h.
[0011] Optionally, the detergent comprises hot water and / or dilute acid solution; In the case where the detergent is hot water, the temperature of the hot water is 50°C to 80°C; In the case where the detergent is dilute acid solution, the molar concentration of the dilute acid solution is 0.01 mol / L to 0.2 mol / L.
[0012] Optionally, in the case that the washing agent is a dilute acid solution, the dilute acid solution comprises at least one of acetic acid, citric acid, oxalic acid, hydrochloric acid, sulfuric acid and nitric acid.
[0013] Optionally, a target conductivity of the second washing is less than or equal to 50 mS / cm.
[0014] Optionally, the flow rate of the carbon dioxide is 0.1 L / min to 100 L / min; and / or a target pH of the carbonation reaction is 8.5 to 10.5; and / or the preset sodium content is <1%.
[0015] In a second aspect, the embodiments of the present application provide a flaky alumina, which is prepared by the method of the first aspect; and a ratio of diameter to thickness of the flaky alumina is greater than or equal to 10.
[0016] Compared with the prior art, the above technical solutions provided by the embodiments of the present application have the following advantages: The method for preparing flaky alumina using electrolyte waste liquid provided by the embodiments of the present application uses electrolyte waste liquid containing aluminum ions and sodium ions as an aluminum source, and through a carbonation reaction of carbon dioxide, aluminum ions in the electrolyte waste liquid form a hydroxide precipitate, and then the content of sodium ions in the hydroxide precipitate is reduced through a first washing, which is conducive to the subsequent formation of a γ-type alumina precursor with good morphology. In addition, soluble sodium chloride, potassium chloride and sodium sulfate are used to form a composite molten salt system, and through a molten salt reaction of the composite molten salt system and the γ-type alumina precursor, the γ-type alumina precursor can be converted into α-Al2O3 in a molten salt system without fluorides, and the three-dimensional growth of alumina crystals is limited, so that Al2O3 is forced to grow along the (001) basal plane (hexagonal sheet layer direction) without adsorption, thereby forming a flaky alumina crude product with a large diameter-to-thickness ratio. Finally, through a second washing, impurity elements in the flaky alumina crude product can be fully removed, and subsequent modification of the flaky alumina by strong acid is not needed, so that flaky alumina with a high diameter-to-thickness ratio can be prepared without using fluorides and strong acids. BRIEF DESCRIPTION OF DRAWINGS
[0017] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the accompanying drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, for those of ordinary skill in the art, other drawings can be obtained based on these drawings without any creative effort.
[0019] Figure 1 A flow chart of a method for preparing flaky alumina using electrolyte waste liquid is provided in the embodiments of the present application. Figure 2 A scanning electron microscope image of flaky alumina provided in Embodiment 1 of the present application is provided. Figure 3 A scanning electron microscope image of flaky alumina provided in Embodiment 2 of the present application is provided. Figure 4 A scanning electron microscope image of flaky alumina provided in Embodiment 3 of the present application is provided. Figure 5 A scanning electron microscope image of flaky alumina provided in Embodiment 4 of the present application is provided. Figure 6 A scanning electron microscope image of flaky alumina provided in Embodiment 5 of the present application is provided. Figure 7 A scanning electron microscope image of flaky alumina provided in Comparative Example 1 of the present application is provided. Figure 8 A scanning electron microscope image of flaky alumina provided in Comparative Example 2 of the present application is provided. Figure 9 A scanning electron microscope image of flaky alumina provided in Comparative Example 3 of the present application is provided. DETAILED DESCRIPTION
[0020] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without any creative effort belong to the scope of protection of the present application.
[0021] The range descriptions described in the present application, such as numerical range, ratio range, etc., include all possible sub-ranges and single values within the range, for example, the range description of "1 to 6" or "1~6" covers all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms "comprise" and the like used herein mean "include but not limited to"; the terms "first", "second" and the like are used only to distinguish different entities or operations, and do not imply actual sequence or relationship; "and / or" means that multiple cases can exist alone or simultaneously; "at least one", "multiple", "at least one" and the like refer to any combination of the corresponding objects, including single or multiple combinations. The ratio relationship involved in the present application, such as mass ratio, molar ratio, etc., should be understood as the corresponding relationship between the front and the rear in the ratio. The raw materials, reagents, instruments and equipment used in the present application can be purchased or prepared by existing methods.
[0022] It should be noted that for the prior art (1) described in the background art, the inventors found that the technology requires additional preparation of a precursor, resulting in a longer production process of the flaky alumina, and the separation of the molten salt system from the flaky alumina is more difficult, increasing the complexity of the subsequent water washing step. For the prior art (2) described in the background art, the inventors found that although the aspect ratio of the flaky alumina product obtained by the technology can reach 60, the technology relies on a fluorine-containing compound system, which not only increases the corrosion risk of related equipment, but also increases the environmental protection pressure of the overall preparation technology. For the prior art (3) described in the background art, the inventors found that the technology still has the corrosion risk and environmental protection pressure introduced by the fluorine-containing compound system, and the flaky alumina obtained by the technology also needs a deep salt washing operation, making the process flow more complex. For the prior art (4) described in the background art, the inventors found that the reaction temperature in the process of producing flaky alumina by the technology is relatively high, usually at 1100℃ to 1300℃, which makes the overall energy consumption of the technology higher, and the consumption of molten salt by the technology is large. For the prior art (5) described in the background art, the inventors found that the mass ratio between the molten salt and the amorphous alumina powder used by the technology, as well as the range of the addition amount of α-Al2O3 seed powder, is relatively narrow, and the purity of the molten salt used is high, and a large amount of water is required for subsequent washing of the flaky alumina product. This shows that the existing molten salt system still cannot produce flaky alumina without fluorine-containing compounds or strong acid washing, which makes the existing molten salt system for producing flaky alumina have the problems of equipment corrosion, high environmental protection pressure and high production cost.
[0023] In addition, the electrolyte waste liquid of aluminum-air batteries has unique compositional characteristics: except for the high content of Na, K and Al, the content of other impurity elements (such as Fe, Si, Cu, Zn, Mg, Mn and Ti) is very low. This makes the purity level of the aluminum-containing components in the electrolyte waste liquid close to that of high-purity alumina. Moreover, the solution system has significant advantages over ordinary industrial alumina solid raw materials. At the same time, the cost of using the electrolyte waste liquid as raw material is significantly lower than that of ordinary industrial alumina solid raw materials.
[0024] Therefore, replacing the aluminum source in the traditional molten salt system with the electrolyte waste liquid of aluminum-air batteries can effectively reduce the production cost of sheet alumina and provide unique resource and cost advantages for the preparation of high-performance sheet alumina.
[0025] Figure 1 An exemplary schematic diagram of a method for preparing sheet-like alumina using electrolyte waste liquid provided in an embodiment of this application is shown. like Figure 1 As shown in the embodiment of this application, a method for preparing flake-shaped alumina using electrolyte waste liquid is provided. The electrolyte waste liquid contains sodium ions and aluminum ions, and the molar concentration of aluminum ions is greater than or equal to 0.5 mol / L. The method includes: S1. Carbon dioxide is used to perform a carbonation reaction on the electrolyte waste liquid, so that the aluminum ions form aluminum hydroxide, and aluminum hydroxide precipitate is obtained; S2. The aluminum hydroxide precipitate is first washed with detergent to obtain a washed aluminum hydroxide solid with a preset sodium content; S3. The washed aluminum hydroxide solid with a preset sodium content is calcined to obtain a γ-type alumina precursor; S4. The composite molten salt system and the γ-alumina precursor are subjected to a molten salt reaction, so that the γ-alumina precursor grows oriented along the crystal basal plane to obtain a plate-like crude alumina product; wherein, the composite molten salt system is a mixture of sodium chloride, potassium chloride and sodium sulfate; S5. The crude flake alumina is subjected to a second washing to obtain the flake alumina product.
[0026] It should be noted that the molten salt reaction can be carried out in a high-purity alumina crucible. To ensure the fullness of the molten salt reaction, the height of the filler in the alumina crucible should be controlled to 2 / 3 of the crucible height, and an alumina cover should be used for sealing.
[0027] It should be noted that this molten salt reaction can be carried out using a high-temperature box-type resistance furnace as the heating device, in an air atmosphere, to raise the temperature of the composite molten salt system and the γ-type alumina precursor to the temperature required for the molten salt reaction. Alternatively, in the industrial production stage, large-scale heating equipment such as roller kilns, pusher kilns, tunnel kilns, or box kilns can be used to replace this high-temperature box-type resistance furnace.
[0028] It should be noted that this carbonation reaction, in addition to promoting Al 3+ In addition to forming a precipitate, it also causes a small amount of metallic impurities to co-precipitate during the precipitation process, effectively reducing the impurity level of the aluminum hydroxide precipitate.
[0029] It should be noted that the first wash is a short, quick wash, and the time of the first wash is less than or equal to 2 hours.
[0030] It should be noted that the washed aluminum hydroxide solid with a preset sodium content formed after the first washing can be dried before calcination to avoid the large amount of water in the washed aluminum hydroxide solid affecting the formation of the γ-type alumina precursor during the calcination stage.
[0031] It should be noted that the method for preparing sheet-like alumina using electrolyte waste liquid provided in this application embodiment employs three core strategies: resource utilization of electrolyte waste liquid, precise control of sodium content, and directional induction by composite molten salt. This method prepares sheet-like alumina with a high aspect ratio under fluoride-free and strong acid conditions. The specific mechanism is as follows: I. Carbonation-washing: Purification of low-sodium precursors from electrolyte waste liquid 1. Carbon dioxide carbonation controls the sodium content of the precursor: Al in electrolyte waste liquid 3+ (Mass concentration ≥ 0.5 mol / L) can react with carbon dioxide to form aluminum hydroxide precipitate, while Na + The ions inherent in the electrolyte waste liquid do not precipitate under the acidic / alkaline conditions of carbonation, but remain in the mother liquor. Al can be controlled by adjusting the CO2 flow rate and reaction time. 3+ with Na + Preliminary separation. (Compared to traditional acid methods: avoids the introduction of impurities caused by strong acid dissolving the aluminum source, and CO2 is a mild precipitant, resulting in low cost and minimal pollution) 2. Deep sodium removal through water washing The aluminum hydroxide precipitate is washed with deionized water or dilute ammonia (non-strong acid). Based on the negative correlation between sodium content and crystal defects, when the sodium content is <0.1%, there are fewer defects in the alumina crystals, which improves the crystal surface regularity of the γ-type alumina precursor obtained after calcination, providing a high-quality substrate for subsequent directional growth.
[0032] II. Directed Growth of Composite Molten Salt: Fluoride-Free Crystal Facet Modulation 1. Synergistic effect of the NaCl-KCl-Na2SO4 composite molten salt system (1) The NaCl-KCl molten salt system has low eutectic properties (melting point about 650℃): reducing the melting temperature to below 1200℃ (traditional molten salt systems need to maintain the temperature above 1400℃), reducing the energy consumption of γ→α phase transition, while the liquid molten salt provides ion diffusion channels to accelerate Al2O3 rearrangement.
[0033] (2) Adsorption on Na2SO4 crystal plane: Na2SO4 2- Selective adsorption on the (111) crystal plane (octahedral void plane) of γ-type alumina inhibits crystal growth in this direction, forcing Al2O3 to grow epitaxially along the unadsorbed (001) basal plane (hexagonal lamellar direction) to form thin sheets with a large diameter-to-thickness ratio.
[0034] (3) Optimization of precursor-composite molten salt: Controlling the mass ratio of the composite molten salt system to the precursor ensures that the molten salt encapsulates the precursor particles, creating a microreactor-like reaction environment that restricts the three-dimensional growth of alumina crystals and forces them to expand along two-dimensional lamellar structures. Residual Na in the electrolyte waste liquid... + It can be used as a natural flux in complex molten salt systems without the need for additional fluorides.
[0035] III. Green Post-treatment: Water washing and purification replaces strong acid etching 1. Wash the salt with hot water: The composite molten salt system (NaCl / KCl / Na2SO4) consists entirely of water-soluble molten salts, which can be completely removed by repeated hot water washing (non-hydrofluoric acid), avoiding the corrosion of the alumina's lamellar structure by strong acids (traditional methods generally require strong acid etching of impurities). Furthermore, the wastewater after washing is neutralized with limestone (Ca... 2+ Precipitate SO4 2- The residue produced after limestone neutralization can be recycled and used as building material to achieve the goal of zero emissions for the whole method.
[0036] 2. Calcination-melting synergistic enhancement of crystallization: The γ-type alumina precursor undergoes a process of local melting and directional recrystallization in molten salt: under high temperature conditions, the γ-phase alumina first decomposes into amorphous Al2O3, and then reconstructs into α-Al2O3 sheets along the (001) plane in the molten salt, avoiding the random agglomeration of the traditional solid-state method. In addition, the low-sodium environment can reduce grain boundary defects in alumina, allowing the thickness of the alumina sheets to be controlled between 0.1 μm and 0.3 μm, and the diameter to reach 10 μm to 20 μm.
[0037] IV. Core Guarantee of High-Diameter-Thickness Ratio 1. Sodium content control: Compared with the acid washing method that relies on traditional methods and causes significant pollution, the method provided in this application can precisely control the sodium content in the γ-alumina precursor by combining carbonation and washing, so that the sodium content is maintained below 1% after the first washing. This can reduce the sodium content in the γ-alumina precursor, ensure the accurate addition of sodium in the composite molten salt system, reduce the stress at the alumina grain boundaries in the subsequent molten salt reaction, and promote the smooth growth of lamellar alumina.
[0038] 2. Molten Salt Directionality: Compared to traditional methods that rely on highly toxic fluoride induction, the method provided in this application utilizes sulfate adsorption, via SO4... 2- Selectively inhibiting the vertical growth of alumina can effectively reduce the amount of fluoride used.
[0039] 3. Advantages of post-processing: Compared with the hydrofluoric acid etching relied upon by traditional methods, the method provided in this application can avoid the high-risk wastewater generated by hydrofluoric acid etching through hot water circulation washing. At the same time, the water washing waste liquid generated by hot water circulation washing can be recycled and reused, which meets environmental protection requirements and is suitable for large-scale production.
[0040] In summary, the present application provides a method for preparing sheet-like alumina using electrolyte waste liquid. This method achieves high aspect ratio and low cost preparation of sheet-like alumina under fluoride-free and strong acid-free conditions by utilizing sodium resources in situ from the electrolyte waste liquid (converting it into molten salt components), green regulation through crystal surface adsorption (sulfate replacing fluoride), and deep purification through gentle washing (hot water replacing strong acid). At the same time, it solves the environmental protection problem of electrolyte waste liquid treatment and has significant industrial application value.
[0041] In some alternative embodiments, the mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following: m1:m2 = (2 to 6):1.
[0042] In these embodiments, the composite molten salt system with a mass ratio of (2 to 6):1 to the γ-alumina precursor can promote the accelerated rearrangement of alumina crystals in the γ-alumina precursor during the molten salt reaction and cause Al2O3 to grow along the (001) basal plane to form a high aspect ratio sheet alumina product; in addition, the molten salt system has good water solubility and can be removed by a second washing, without the need for subsequent modification of the sheet alumina with strong acid.
[0043] The mass m1 of the composite molten salt system can be 2, 3, 4, 5 or 6.
[0044] In some alternative embodiments, the amounts of sodium chloride n1, potassium chloride n2, and sodium sulfate n3 satisfy: n1:n2:n3 = (0.8 to 2):(0.5 to 1.5):(0.8 to 1.5).
[0045] In these embodiments, the molar ratio of sodium chloride, potassium chloride, and sodium sulfate of (0.8 to 2):(0.5 to 1.5):(0.8 to 1.5) effectively promotes the accelerated rearrangement of alumina crystals in the γ-alumina precursor during the molten salt reaction, restricts the three-dimensional growth of alumina crystals, and forces the alumina crystals to expand along two-dimensional lamellar layers, ultimately forming a high aspect ratio lamellar alumina product. Furthermore, sodium chloride, potassium chloride, and sodium sulfate have good water solubility and can be removed by a second washing process, eliminating the need for subsequent modification of the lamellar alumina with strong acids.
[0046] The amount of sodium chloride, n1, can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or 2.0.
[0047] The amount of potassium chloride, n2, can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5.
[0048] The amount of sodium sulfate, n3, can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5.
[0049] In some alternative embodiments, the temperature of the molten salt reaction is 950°C to 1200°C, and the reaction time is 1 hour to 24 hours.
[0050] In these embodiments, a molten salt reaction at a temperature of 950°C to 1200°C and a time of 1 h to 24 h allows for a full reaction between the composite molten salt system and the γ-alumina precursor. The composite molten salt system promotes accelerated rearrangement of alumina crystals in the γ-alumina precursor and restricts the three-dimensional growth of alumina crystals, forcing the alumina crystals to expand along two-dimensional lamellae, ultimately forming a sheet-like alumina product with a high aspect ratio.
[0051] The temperature for the molten salt reaction can be 950℃, 960℃, 970℃, 980℃, 990℃, 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃.
[0052] The reaction time for the molten salt can be 1h, 2h, 3h, 4h, 5h, 10h, 15h, 20h or 24h.
[0053] In some alternative embodiments, the calcination temperature is from 450°C to 850°C, and the calcination time is from 0.5 h to 10.0 h.
[0054] In these embodiments, calcination at a temperature of 450°C to 850°C for 0.5 h to 10.0 h can transform the washed aluminum hydroxide solid into γ-alumina precursors, which are beneficial for subsequent molten salt reactions to form sheet-like alumina products with high aspect ratios.
[0055] The calcination temperature can be 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, or 850℃.
[0056] The calcination time can be 0.5h, 1.0h, 2.0h, 3.0h, 4.0h, 5.0h, 6.0h, 7.0h, 8.0h, 9.0h or 10.0h.
[0057] In some alternative embodiments, the detergent comprises hot water and / or a dilute acid solution; When the detergent is hot water, the temperature of the hot water is 50°C to 80°C; When the detergent is a dilute acid solution, the molar concentration of the dilute acid solution is from 0.01 mol / L to 0.2 mol / L.
[0058] In these embodiments, hot water at a temperature of 50°C to 80°C is used as the detergent, which can effectively remove impurity ions (mainly Na+) from the aluminum hydroxide precipitate. + This reduces the content of impurity ions in the aluminum hydroxide precipitate, resulting in a sodium content of less than 0.1% in the washed aluminum hydroxide solid, which is beneficial for the molten salt reaction. Alternatively, a dilute acid solution with a molar concentration of 0.01 mol / L to 0.2 mol / L can be used as a washing agent. Compared to hot water washing, this method removes sodium... + In addition, dilute acid solutions can also remove potassium precipitate from aluminum hydroxide. + The presence of alkali metal ions and the presence of dilute acid solutions can prevent excessive corrosion of γ-Al2O3 grains, thus preserving the morphology of the γ-alumina precursor.
[0059] The temperature of the hot water can be 50℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 80℃.
[0060] The molar concentration of the dilute acid solution can be 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.10 mol / L, 0.15 mol / L, or 0.20 mol / L.
[0061] In some alternative embodiments, when the detergent is a dilute acid solution, the dilute acid solution includes at least one of acetic acid, citric acid, oxalic acid, hydrochloric acid, sulfuric acid, and nitric acid.
[0062] In these embodiments, a dilute acid solution comprising at least one of acetic acid, citric acid, oxalic acid, hydrochloric acid, sulfuric acid, and nitric acid can be used to remove Na+ precipitate from aluminum hydroxide. + K + Alkali metal ions are used to prevent excessive corrosion of γ-Al2O3 grains and ensure the morphology of the γ-type alumina precursor.
[0063] It should be noted that the acetic acid in this dilute acid solution has the characteristics of low acidity and is not likely to cause excessive corrosion to γ-Al2O3 grains. At the same time, compared with other dilute acid solutions, acetic acid has a lower cost and does not introduce new impurities that are difficult to remove, so it is suitable for industrial applications.
[0064] In some alternative embodiments, the target conductivity of the second wash is less than or equal to 50 mS / cm.
[0065] In these embodiments, a second wash with a target conductivity of less than or equal to 50 mS / cm indicates that impurity ions in the crude flake alumina have been sufficiently removed, resulting in a high-purity flake alumina product.
[0066] In some optional embodiments, the carbon dioxide flow rate is from 0.1 L / min to 100 L / min; and / or The target pH for the carbonation reaction is 8.5 to 10.5; and / or The preset sodium content is <1%.
[0067] In these embodiments, introducing carbon dioxide at a flow rate of 0.1 L / min to 100 L / min allows the carbonation reaction to proceed fully, reducing the Al content in the electrolyte waste liquid. 3+ OH- formed by dissolving carbon dioxide - The reaction forms aluminum hydroxide precipitate, and simultaneously promotes the participation of some impurity ions in the electrolyte waste liquid, which helps reduce the impurity level in the aluminum hydroxide precipitate; in addition, the carbonic acid reaction of carbon dioxide precipitates Al in the electrolyte waste liquid. 3+This method avoids the corrosion and introduction of exogenous ions caused by using strong acids for conditioning, and the resulting Al(OH)3 precipitate has a uniform particle size distribution and good dispersibility, which is beneficial for subsequent calcination and the formation of plate-like α-Al2O3. Furthermore, the carbonation reaction with a target pH of 8.5 to 10.5 indicates that Al in the electrolyte waste liquid... 3+ Aluminum hydroxide precipitate has been fully formed. In addition, the preset sodium content of less than 1% can reduce the sodium content in the γ-alumina precursor, ensuring the accurate addition of sodium in the composite molten salt system. This improves the crystal surface regularity of the γ-alumina precursor obtained after calcination, providing a high-quality substrate for the subsequent directional growth of alumina crystals.
[0068] The carbon dioxide flow rate can be 0.1 L / min, 0.5 L / min, 1.0 L / min, 1.5 L / min, 2.0 L / min, 2.5 L / min, 3.0 L / min, 5.0 L / min, 10.0 L / min, 15.0 L / min, 30.0 L / min, 50.0 L / min, or 100.0 L / min.
[0069] The target pH for the carbonation reaction can be 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.5, 10.0, or 10.5.
[0070] The preset sodium content can be 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.50%, 0.75%, or 1.00%.
[0071] Based on a general inventive concept, embodiments of this application provide a sheet-like alumina, which is prepared by the method described above; the aspect ratio of the sheet-like alumina is greater than or equal to 10.
[0072] The sheet-like alumina is obtained based on the above method. The specific steps of the method can be referred to the above embodiments. Since the sheet-like alumina adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.
[0073] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national / industry standards; if there is no corresponding national / industry standard, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0074] Example 1 like Figure 1As shown, a method for preparing sheet-like alumina using electrolyte waste liquid, wherein the electrolyte waste liquid contains sodium ions and aluminum ions, the aluminum ions exist in the form of Al(OH)4⁻, and the molar concentration of aluminum ions is 0.5 mol / L, comprising: S1. Carbon dioxide is used to carbonate 1000 mL of aluminum-air electrolyte waste liquid, causing aluminum ions to form aluminum hydroxide, and aluminum hydroxide precipitate is obtained; S2. Wash the aluminum hydroxide precipitate once with detergent to obtain washed aluminum hydroxide solid with a preset sodium content; S3. Calcining the washed aluminum hydroxide solid with a preset sodium content to obtain a γ-type alumina precursor; S4. The composite molten salt system and the γ-alumina precursor are subjected to a molten salt reaction, which causes the γ-alumina precursor to grow oriented along the crystal basal plane to obtain a plate-like crude alumina product; wherein, the composite molten salt system is a mixture of sodium chloride, potassium chloride and sodium sulfate; S5. Perform a second washing on the crude flake alumina to obtain the flake alumina product.
[0075] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following ratio: m1:m2=4:1.
[0076] The amounts of sodium chloride (n1), potassium chloride (n2), and sodium sulfate (n3) satisfy the following formula: n1:n2:n3 = 1:1:1.
[0077] The temperature of the molten salt reaction was 1080℃, and the reaction time was 4 hours.
[0078] The calcination temperature was 550℃ and the calcination time was 1.0h.
[0079] Detergent includes hot water; When the detergent is hot water, the temperature of the hot water is 70℃.
[0080] The target conductivity for the second wash is less than or equal to 13 mS / cm.
[0081] The carbon dioxide flow rate is 10 L / min; The target pH for the carbonation reaction is 9.5; The preset sodium content is less than 1%.
[0082] Example 2 Compared to Example 1, the differences in this example are as follows, while the rest are the same: The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following ratio: m1:m2=3:1.
[0083] The temperature of the molten salt reaction was 1020℃, and the reaction time was 2 hours.
[0084] The calcination temperature was 600℃ and the calcination time was 1.0h.
[0085] The detergent is a dilute acid solution; When the detergent is a dilute acid solution, the molar concentration of the dilute acid solution is 0.05 mol / L.
[0086] When the detergent is a dilute acid solution, the dilute acid solution is hydrochloric acid.
[0087] The target conductivity for the second wash is less than or equal to 50 mS / cm.
[0088] The carbon dioxide flow rate is 1 L / min to 5 L / min; Example 3 Compared to Example 1, the differences in this example are as follows, while the rest are the same: The amounts of sodium chloride (n1), potassium chloride (n2), and sodium sulfate (n3) satisfy the following formula: n1:n2:n3 = 2:1:1.
[0089] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following ratio: m1:m2=5:1.
[0090] The temperature of the molten salt reaction was 1120℃, and the reaction time was 2 hours.
[0091] Example 4 Compared to Example 1, the differences in this example are as follows, while the rest are the same: The molar concentration of aluminum ions in the electrolyte waste liquid is 0.8 mol / L, and the volume of the electrolyte waste liquid is 1500 mL.
[0092] The first wash was performed twice.
[0093] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following condition: m1:m2=3.5:1.
[0094] The amounts of sodium chloride (n1), potassium chloride (n2), and sodium sulfate (n3) satisfy the following ratio: n1:n2:n3 = 1.5:1:1.
[0095] The temperature for the molten salt reaction was 1050℃, and the reaction time was 5 hours.
[0096] The calcination temperature was 500℃ and the calcination time was 2.0h.
[0097] The target pH for the carbonation reaction is 9.0.
[0098] Example 5 Compared to Example 1, the differences in this example are as follows, while the rest are the same: The molar concentration of aluminum ions in the electrolyte waste liquid is 0.6 mol / L, and the volume of the electrolyte waste liquid is 1200 mL.
[0099] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following condition: m1:m2=4.5:1.
[0100] The amounts of sodium chloride (n1), potassium chloride (n2), and sodium sulfate (n3) satisfy the following ratio: n1:n2:n3 = 1.2:1:1.
[0101] The temperature of the molten salt reaction was 1100℃, and the reaction time was 3 hours.
[0102] The calcination temperature was 580℃ and the calcination time was 1.5h.
[0103] The detergent is a dilute acid solution; When the detergent is a dilute acid solution, the molar concentration of the dilute acid solution is 0.01 mol / L.
[0104] When the detergent is a dilute acid solution, the dilute acid solution is acetic acid.
[0105] The target pH for the carbonation reaction is 10.0.
[0106] Comparative Example 1 Compared to Example 1, the differences in this comparative example are as follows, while the rest are the same: The electrolyte waste liquid was directly calcined without undergoing carbonation or first washing to obtain the γ-type alumina precursor.
[0107] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following ratio: m1:m2=4:1.
[0108] The temperature of the molten salt reaction was 1080℃, and the reaction time was 4 hours.
[0109] The calcination temperature was 550℃ and the calcination time was 1.0h.
[0110] Comparative Example 2 Compared to Example 1, the differences in this comparative example are as follows, while the rest are the same: Instead of using a complex molten salt system, sodium sulfate is used directly as a substitute.
[0111] The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following ratio: m1:m2=4:1.
[0112] The temperature of the molten salt reaction was 1100℃, and the reaction time was 4 hours.
[0113] Comparative Example 3 Compared to Example 1, the differences in this comparative example are as follows, while the rest are the same: The temperature of the molten salt reaction was 900℃, and the reaction time was 4 hours.
[0114] Comparative Example 4 Compared to Example 1, the differences in this comparative example are as follows, while the rest are the same: The first wash is not performed, meaning the sodium content is not pre-controlled below 1%.
[0115] Relevant experimental and effect data: Flake alumina products from each embodiment and comparative example were collected, and the aspect ratio and impurity elements of the flake alumina products were measured. The results are shown in Table 1 and 2. Figures 2 to 9 As shown.
[0116] 1. Method for determining the aspect ratio: The sheet-like alumina product is ultrasonically dispersed in anhydrous ethanol to obtain a mixed suspension. The mixed suspension is dropped onto a silicon wafer and dried. The dried silicon wafer is observed using a scanning electron microscope (SEM, magnification 500 to 2000x). At least 100 individual particles are randomly selected from the observation field, and their diameter D and thickness T are measured respectively. The aspect ratio is the ratio of D / T, and the average value obtained is the aspect ratio of the sheet-like alumina product. The results are as follows: Figures 2 to 9 .
[0117] 2. The method for determining impurity elements is as follows: The flake alumina product is digested with a mixed acid solution (such as nitric acid and phosphoric acid, the specific amount of which is determined according to the actual digestion volume), and then quantitative analysis is performed using inductively coupled plasma optical emission spectrometry (ICP-OES) or inductively coupled plasma mass spectrometry (ICP-MS). The target elements for quantitative analysis include Na, Fe, Si, Cu, Zn, Mg, Mn and Ti, etc.
[0118] Table 1. Aspect ratio and impurity element content distribution of the sheet-like alumina products in each embodiment and comparative example.
[0119] As shown in Table 1, the method for preparing sheet-like alumina using electrolyte waste provided in this application achieves high aspect ratio and low cost preparation of sheet-like alumina under fluoride-free and strong acid-free conditions through in-situ utilization of sodium resources in the electrolyte waste (converting it into molten salt components), green regulation of crystal surface adsorption (sulfate replacing fluoride), and deep purification through gentle washing (hot water replacing strong acid). This method also solves the environmental treatment problem of electrolyte waste and has significant industrial application value. The final sheet-like alumina product has an aspect ratio of over 10, and the Na content of the impurity element is below 290 ppm, with the total amount of impurity elements other than Na below 200 ppm.
[0120] Compared to Example 1, Comparative Example 1 skipped the carbonation reaction and the first washing, directly calcining to obtain the γ-alumina precursor. This resulted in a higher concentration of impurities in the γ-alumina precursor, affecting the subsequent molten salt reaction. Figure 7 It can be seen that although the average aspect ratio of the final flake alumina product reached 18, the flake morphology of the flake alumina product was poor, and the whole product showed a large number of irregular agglomerations of particles, and the content of impurity element Na was above 1000ppm.
[0121] Compared to Example 1, by Figure 8 It can be seen that Comparative Example 2 does not use the composite molten salt system, but directly uses sodium sulfate to replace the composite molten salt system. This makes the average aspect ratio of the flake alumina product reach the range of 6 to 8. However, the flake alumina product has a small surface size and uneven thickness, resulting in poor dispersion of the flake alumina product.
[0122] Compared to Example 1, by Figure 9 It can be seen that the molten salt reaction temperature of Comparative Example 3 is relatively low, which makes it difficult for the molten salt reaction to proceed completely. As a result, most of the γ-type alumina precursors still exist in the γ phase, while a small amount of the γ-type alumina precursors are transformed into α-phase lamellar alumina products. In the final product, the mass of lamellar alumina products is less than or equal to 30% of the total product mass, and the product performance is poor.
[0123] Compared to Example 1, Comparative Example 4 did not use hot water or dilute acid solution for the first wash, which made it difficult to remove impurities from the aluminum hydroxide precipitate, resulting in an affected morphology of the flake alumina and a higher content of impurity elements in the final flake alumina.
[0124] In addition, during the aspect ratio determination stage, the average particle size of the alumina product in Example 1 was 10 μm and the thickness was 0.7 μm, exhibiting good dispersibility; the alumina product in Example 2 exhibited a highly flaky structure; the alumina product in Example 3 had an average particle size of 13.8 μm and a thickness of 0.9 μm, with slightly larger grain thickness; the alumina product in Example 4 had an average particle size of 11 μm and a thickness of 1.0 μm, showing good uniformity; and the alumina product in Example 5 had an average particle size of 8 μm and a thickness of 0.5 μm, with the lowest residual content of the impurity element Na.
[0125] In summary, the embodiments of this application provide a method for preparing sheet-like alumina using electrolyte waste liquid. This method employs three core strategies: resource utilization of electrolyte waste liquid, precise control of sodium content, and directional induction by composite molten salt. Under fluoride-free and strong acid conditions, it prepares sheet-like alumina with a high aspect ratio. The final product obtained is sheet-like aluminum hydroxide with an aspect ratio of 10 or higher and a Na content of less than 290 ppm. This method not only achieves high-value utilization of aluminum-air battery electrolyte waste liquid but also boasts advantages such as low cost, good environmental performance, and excellent product performance, making it highly practical and worthy of widespread application.
[0126] Furthermore, this application provides a method for preparing sheet-like alumina using electrolyte waste liquid. This method, for the first time, couples aluminum-air battery electrolyte waste liquid with a fluoride-free composite molten salt system, improving the high-value utilization rate of aluminum resources in the electrolyte waste liquid. Through carbonation reaction and pretreatment with a first wash, high-purity aluminum hydroxide precipitate can be obtained. Then, using a composite molten salt system composed of sodium chloride, potassium chloride, and sodium sulfate, the alumina crystals in the γ-type alumina precursor can be accelerated to rearrange, and the three-dimensional growth of alumina crystals can be restricted, forcing the alumina crystals to expand along two-dimensional lamellae. Ultimately, a sheet-like alumina product with a high aspect ratio can be formed, avoiding corrosion and environmental problems caused by the addition of fluoride-containing mineralizers. Simultaneously, these composite molten salt systems use soluble salts, which can be easily removed by a second wash, reducing the consumption of the composite molten salt system and the workload of the second wash. This achieves resource utilization of electrolyte waste liquid and stable preparation of high-performance sheet-like alumina products, demonstrating significant innovation and practical value.
[0127] In addition, this application provides a method for preparing flake alumina using electrolyte waste liquid. This method directly uses aluminum-air battery electrolyte waste liquid as an aluminum source and salt source, while avoiding the use of fluoride mineralizers and the need for strong acid etching. This not only significantly reduces the risk of equipment corrosion and fluoride residue, but also significantly reduces the production cost of flake alumina.
[0128] Furthermore, this application provides a method for preparing flake-shaped alumina using waste electrolyte. The waste electrolyte from aluminum-air batteries used in this method contains a large amount of alkaline ions such as sodium and potassium. Directly removing impurities from the battery electrolyte waste is difficult. However, in the molten salt reaction stage of this method, these alkaline ions are effectively repelled, preventing them from entering the alumina lattice, thus obtaining flake-shaped alumina products with a purity of over 99.5%. Therefore, this method can also be used as a purification technology for aluminum-air battery electrolyte waste, facilitating the multi-dimensional utilization and efficient value-added processing of aluminum-air battery electrolyte waste.
[0129] In addition, the embodiments of this application provide a method for preparing flake alumina using electrolyte waste liquid. The composite molten salt system used in this method is compatible with existing molten salt methods or ceramic additive production processes and can be directly integrated into existing production lines, which facilitates the large-scale promotion and application of flake alumina products.
[0130] Furthermore, the embodiments of this application provide a sheet-like alumina with an aspect ratio generally above 10, and the impurity element content of the sheet-like alumina is below 300 ppm, and the total impurity element content is below 0.05%, with the overall purity of the sheet-like alumina product being above 99.5%.
[0131] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A method for preparing flake-shaped alumina using electrolyte waste liquid, wherein the electrolyte waste liquid contains sodium ions and aluminum ions, and the molar concentration of aluminum ions is greater than or equal to 0.5 mol / L, characterized in that, The method includes: The electrolyte waste liquid is carbonated using carbon dioxide, causing the aluminum ions to form aluminum hydroxide, resulting in aluminum hydroxide precipitate. The aluminum hydroxide precipitate is first washed with detergent to obtain a washed aluminum hydroxide solid with a preset sodium content. The washed aluminum hydroxide solid with a preset sodium content is calcined to obtain a γ-type alumina precursor. The composite molten salt system and the γ-alumina precursor are subjected to a molten salt reaction, causing the γ-alumina precursor to grow oriented along the crystal basal plane to obtain a plate-like crude alumina product; wherein, the composite molten salt system is a mixture of sodium chloride, potassium chloride and sodium sulfate; The crude flake alumina is subjected to a second washing to obtain the flake alumina product.
2. The method according to claim 1, characterized in that, The mass m1 of the composite molten salt system and the mass m2 of the γ-type alumina precursor satisfy the following: m1:m2 = (2 to 6):
1.
3. The method according to claim 1, characterized in that, The amounts of sodium chloride (n1), potassium chloride (n2), and sodium sulfate (n3) satisfy the following ratio: n1:n2:n3 = (0.8 to 2):(0.5 to 1.5):(0.8 to 1.5).
4. The method according to claim 1, characterized in that, The temperature of the molten salt reaction is 950°C to 1200°C, and the reaction time is 1 hour to 24 hours.
5. The method according to claim 1, characterized in that, The calcination temperature is from 450°C to 850°C, and the calcination time is from 0.5h to 10.0h.
6. The method according to claim 1, characterized in that, The detergent includes hot water and / or a dilute acid solution; When the detergent is hot water, the temperature of the hot water is 50°C to 80°C; When the detergent is a dilute acid solution, the molar concentration of the dilute acid solution is from 0.01 mol / L to 0.2 mol / L.
7. The method according to claim 6, characterized in that, When the detergent is a dilute acid solution, the dilute acid solution includes at least one of acetic acid, citric acid, oxalic acid, hydrochloric acid, sulfuric acid, and nitric acid.
8. The method according to claim 1, characterized in that, The target conductivity of the second wash is less than or equal to 50 mS / cm.
9. The method according to claim 1, characterized in that, The carbon dioxide flow rate is from 0.1 L / min to 100 L / min; and / or The target pH for the carbonation reaction is 8.5 to 10.5; and / or The preset sodium content is <1%.
10. A type of sheet-like alumina, characterized in that, The sheet-like alumina is prepared by the method according to any one of claims 1 to 9; the aspect ratio of the sheet-like alumina is greater than or equal to 10.
Citation Information
Cited By
A method for synthesizing high crystallinity platelet alumina
CN122403478A